বাংলাদেশে যৌনতা বিক্রি, জীবনের দামে কেনা জীবিকা - কুররাতুল-আইন-তাহমিনা.; Moṛala, Śiśira; Society for Environment and Human Development (Dhaka, Bangladesh) (ঢাকা : সোসাইটি ফর এনভায়রনমেন্ট এন্ড হিউম্যান ডেভেলপমেণ্ট (সেড), 2000)
Study on prostitution in Bangladesh.
Includes bibliographical references (p. 210-213).
In Bengali.
Keywords: Prostitution -- Bangladesh